The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.yebeh.2021.108261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on people with epilepsy: Findings from the Brazilian arm of the COV-E study

Abstract: The COVID-19 pandemic has had an unprecedented impact on people and healthcare services. The disruption to chronic illnesses, such as epilepsy, may relate to several factors ranging from direct infection to secondary effects from healthcare reorganization and social distancing measures. Objectives As part of the COVID-19 and Epilepsy (COV-E) global study, we ascertained the effects of COVID-19 on people with epilepsy in Brazil, based on their perspectives and those of their caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(57 reference statements)
3
5
0
2
Order By: Relevance
“…These findings are further supported by a recent study that reported that 57.1% of PWE and 21.5% of caregivers endorsed significant psychological distress 23 . Deterioration of mood and increased emotional distress in people with epilepsy during the pandemic has also been observed in the UK and Brazilian arms of this study, 16,17 as well as multiple others 1,14,15,18 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are further supported by a recent study that reported that 57.1% of PWE and 21.5% of caregivers endorsed significant psychological distress 23 . Deterioration of mood and increased emotional distress in people with epilepsy during the pandemic has also been observed in the UK and Brazilian arms of this study, 16,17 as well as multiple others 1,14,15,18 …”
Section: Discussionsupporting
confidence: 91%
“… 12 People with epilepsy have experienced worsening of seizures, greater emotional distress, and sleep disruption during this pandemic. 13 , 14 , 15 , 16 , 17 , 18 This reported emotional distress and sleep disruption was similar to the general population, with numbers reported as high as 30% of people citing sleep disturbances, and 71% reporting emotional distress. 19 A recent meta‐analysis has suggested that people with epilepsy may be at greater risk of poorer COVID‐19 outcomes, particularly disease severity and mortality.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The World Health Organization, China office reported a new strain of SARS infection (severe acute respiratory syndrome) in Wuhan, China, in late December 2019 (1)(2)(3)(4)(5). Accordingly, health experts recognized this fatal viral disease as SARS-CoV-2 (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Проблемы психического здоровья и важность оптимального общения имеют решающее значение в эти трудные времена. Службы здравоохранения должны найти тонкие подходы и извлечь уроки из общего международного опыта для обеспечения оптимального ухода за людьми с эпилепсией[24]. Этот необычный опыт проясняет необходимость создания телемедицинских услуг и домашнего лечения эпилепсии[25], включая амбулаторную ЭЭГ, домашнее видео и доставку лекарств по месту жительства пациентов для оказания непрерывной медицинской помощи[26,27,28].Также стоит отметить, что, согласно данным R. von Wrede, J. Pukropski, S. Moskau-В рамках проекта ВОЗ «Реабилитация и качество жизни больных эпилепсией» было проведено исследование уровня социальной стигматизации PWE.…”
unclassified